Conspicuous Mobility: The Status Dimensions of the Global Passport Hierarchy. Issue 1 (September 2021) - Harpaz, Yossi
The world's passports are not equal. Travelers from rich countries enjoy extensive travel freedom across the globe, whereas citizens of less developed nations are subject to stringent visa controls. This article examines this global hierarchy from a social cognition perspective, highlighting the status competition around international travel. It analyzes interviews with ninety-eight persons in Serbia and Israel who have acquired a second passport from a European Union country. The interviews illustrate how a social cognition perspective can shed new light on international mobility and global inequality: the analysis suggests that passengers continuously monitored how they and others were treated by border control authorities, perceiving different treatment as indicative of status. Respondents experienced shame when the treatment they received fell short of their expected standards and felt pleasure and pride when treated better than comparable others. Respondents tended to compare their travel freedom to that enjoyed by citizens of nations that they perceived as culturally similar.